Muscle mineral profile of water buffaloes (Bubalus bubalis) reared in different production systems of the Brazilian Eastern Amazon - Rodrigues, Laurena Silva; Silva, Jamile Andréa Rodrigues da; Lourenço-Júnior, José de Brito; Silva, André Guimarães Maciel e; Almeida, André Martinho de; Mourato, Miguel Pedro; Castro, Vinícius Costa Gomes de; Bezerra, Andréia Santana; Silva, Welligton Conceição da; Prates, José António Mestre (Frontiers in Veterinary Science, 2023)
This study aimed to evaluate the influence of three extensive systems, during the dry and rainy seasons, and an intensive (feedlot) system in the Eastern Amazon, on the muscle mineral profile of water buffaloes. In total, twelve male buffaloes, aged between 24 and 36 months, slaughtered in commercial slaughterhouses, were used in each of the systems considered: Marajó island, Santarém, Nova Timboteua and a feedlot. Approximately 5 g of muscle were collected, immediately frozen and freeze-. The samples were analysed for mineral profile using inductively coupled plasma - optical emission spectrometry (ICP-OES). Significant differences (P <0.05) were found for the concentrations of sodium (Na), magnesium (Mg), phosphorus (P), sulphur (S), copper (Cu), zinc (Zn), and iron (Fe). Extensive and intensive systems showed significant differences (P <0.05) for Na, Ca, S, Cu, and Fe concentrations. The season also influenced (P <0.05) K, Ca, P, S, Zn, and Fe concentrations. The location and season of the year had a significant interaction (P <0.05) for K, Mg, P, Zn, and Fe concentrations. The study showed that the different Amazonian production systems influence (P<0.05) the muscle mineral status in buffalo. The values obtained were, in general, higher in extensive production systems. Therefore, the meat from animals reared in these systems is a good mineral source for human daily needs.